Effect of astigmatism and spherical equivalent correction on contrast sensitivity - Maryam Saffarizadeh; Saeed Rahmani; Alireza Akbarzadeh Baghban; Mohammad Ghassemi-Broumand (International Journal of Ophthalmology)
AIM: To investigate the effect of astigmatism and spherical equivalent (SE) correction on contrast sensitivity (CS). METHODS: In this cross-sectional study, 103 visually normal subjects aged 18 to 36y with bilateral regular astigmatism in range of 1.00 diopter cylinder (DC) to 4.00 DC and normal best-corrected visual acuity (20/20) were recruited. Binocular CS was assessed by linear sine-wave gratings at 1.5, 3, 6, 12, and 18 cycles per degree (cpd), before correction of astigmatism, after full correction of astigmatism by cylindrical spectacle lenses, and after SE of refractive error. The repeated measures ANOVA and Bonferroni test were used to compare the effects of astigmatism correction on logCS. RESULTS: Totally 39 patients were male and 64 patients were female with the mean age of 28.25±5.38y. The average degree of astigmatism in right and left eye was 2.03±0.83 and 2.10±0.78, respectively. Increases in uncorrected astigmatic power correlated with decreases in the logCS, especially at high spatial frequencies. A statistically significant difference in logCS was found between these three cases: before correction of astigmatism, after SE of refractive error, and after full correction of astigmatism by cylindrical spectacle lenses at all frequencies (P<0.001), except at 18 cpd. At 18 cpd, there was no statistically significant difference between logCS before and after SE of refractive error (P=1.0). Also, there was no statistically significant difference in mean CS between with-the-rule (WTR) and against-the-rule (ATR) astigmatism, before correction of astigmatism, after correction of astigmatism with cylindrical lenses, and after SE of refractive error. CONCLUSION: Binocular astigmatism defocus decreases CS depending on the degree of astigmatism power; correction of this will improve patent's quality of vision. Although high astigmatism refractive error (more than 2.00 DC) that is fully corrected by cylindrical spectacle lenses doesn't increase the CS to the maximum value, especially at higher spatial frequencies (12 and 18). Also SE refractive error effects on improving CS in low astigmatism power (less than 2.00 DC), especially at lower spatial frequencies.